Treatment of Graft versus Host Disease with Mesenchymal Stromal Cells: A Phase I Study on 40 Adult and Pediatric Patients - Martino Introna; Giovanna Lucchini; Erica Dander; Stefania Galimberti; Attilio Rovelli; Adriana Balduzzi; Daniela Longoni; Fabio Pavan; Francesca Masciocchi; Alessandra Algarotti; Caterina Micò; Anna Grassi; et al. (2013)
This phase I multicenter study was aimed at assessing the feasibility and safety of intravenous administration of third party bone marrow-derived mesenchymal stromal cells (MSC) expanded in platelet lysate in 40 patients (15 children and 25 adults), experiencing steroid-resistant grade II to IV graft-versus-host disease (GVHD). Patients received a median of 3 MSC infusions after having failed conventional immunosuppressive therapy. A median cell dose of 1.5 × 10(6)/kg per infusion was administered. No acute toxicity was reported. Overall, 86 adverse events and serious adverse events were reported in the study, most of which (72.1%) were of infectious nature. Overall response rate, measured at 28 days after the last MSC injection, was 67.5%, with 27.5% complete response. The latter was significantly more frequent in patients exhibiting grade II GVHD as compared with higher grades (61.5% versus 11.1%, P = .002) and was borderline significant in children as compared with adults (46.7 versus 16.0%, P = .065). Overall survival at 1 and 2 years from the first MSC administration was 50.0% and 38.6%, with a median survival time of 1.1 years. In conclusion, MSC can be safely administered on top of conventional immunosuppression for steroid resistant GVHD treatment. Eudract Number 2008-007869-23, NCT01764100.